Real-time monitoring of cardiac radio-frequency ablation lesion formation using an optical coherence tomography forward-imaging catheter - Fleming, Christine P. (Society of Photo-Optical Instrumentation Engineers, 2010)
Radio-frequency ablation (rfa) is the standard of care for the treatment of cardiac arrhythmias; however, there are no direct measures of the successful delivery of ablation lesions. Optical coherence tomography (OCT) imaging has the potential to provide real-time monitoring of cardiac rfa therapy, visualizing lesion formation and assessing tissue contact in the presence of blood. A rfa-compatible forward-imaging conical scanning probe is prototyped to meet this need. The forward-imaging probe provides circular scanning, with a 2-mm scan diameter and 30-μm spot size. During the application of rf energy, dynamics are recorded at 20 frames per second with a 40-kHz A-line rate. Real-time monitoring of cardiac rfa lesion formation and imaging in the presence of blood is demonstrated ex vivo in a swine left ventricle with a forward, flexible, circular scanning OCT catheter.